Surgical audit of minimally invasive adrenalectomy - A retrospective observational study - Minal S Sonune; Abhay S Dalvi; Abhijit D Ninghot (Asian Journal of Medical Sciences, 2024)
Background: The laparoscopic adrenalectomy technique is currently the standard of care for resecting small benign adrenal lesions in most countries. Some of the reported benefits of laparoscopic adrenalectomy are similar to the benefits of minimally invasive surgery. Aims and Objectives: The objective is to study the types of adrenal tumors and to review outcomes of minimally invasive adrenalectomies. Materials and Methods: In this retrospective observational study, records of 306 patients undergoing minimally invasive adrenalectomy from January 01, 2001 to September 30, 2019, were analyzed. Results: The types of adrenal tumors were found in patients were adrenal adenoma (38), adrenal Cushing’s (47), adrenal carcinoma (14), and pheochromocytoma (207). Pheochromocytoma was the most common type of tumor seen in 68% of the cases. Intensive care unit was required in case of 59 patients while inotropic support was needed for 58 patients while 6 patients required a ventilator in the immediate post-operative period. Surgical site infection was encountered in 29 patients following minimally invasive adrenalectomy. Fever was seen in 18 patients. Pneumonia was the early post-operative complication in 12 patients while paralytic ileus was encountered in 25 patients. Synchronous metastasis to lymph nodes was seen in 12 and tumor bed recurrence was seen in 12 cases each following adrenalectomy. Conclusion: Minimally invasive techniques cause less trauma to patients, have superior visualization, decreased post-operative pain, shorter hospital stays, an earlier return to work and normal activity, and fewer perioperative and post-operative complications.